"In Memory of the Chief Big Foot Massacre": The Wounded Knee Survivors and the Politics of Memory. Issue 1 (February 2015) - Grua, David W.
Abstract: In 1903 the survivors of Wounded Knee erected a monument "In Memory of the Chief Big Foot Massacre" of 1890. the obelisk emerged from the Lakotas' engagement with the politics of memory, as they protested the official memory—the narrative accepted by the government and dominant society—of the "Battle of Wounded Knee" in compensation claims and in their memorial practices.